1990
DOI: 10.1002/art.1780330908
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to signal recognition particle in polymyositis

Abstract: Using immunoprecipitation, we identified 13 patients with antibodies to the signal recognition particle (SRP) from a collection of sera representing 265 polymyasitiddermatomyositis (PM/DM) patients. Antibody reactivity with SRP was confirmed by enzyme-linked immunosorbent assay and immunoprecipitation with isolated dog pancreas SRP. The antibody was present in the serum of 4% of PWDM patients, and 18% of PM/ DM patients with anticytoplasmic antibodies other than anti-Jo-1, but not in patients with other condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
168
1
15

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(197 citation statements)
references
References 54 publications
11
168
1
15
Order By: Relevance
“…These observations are consistent with an earlier report in which anti-SRP was associated with severe PM and a reduced frequency of interstitial lung disease and arthritis, as compared with anti-aminoacyl-tRNA synthetase antibodies (21). These results suggest that anti-SRP may be a marker for a specific clinical subset of patients who have particularly refractory inflammatory muscle disease.…”
Section: Discussionsupporting
confidence: 92%
“…These observations are consistent with an earlier report in which anti-SRP was associated with severe PM and a reduced frequency of interstitial lung disease and arthritis, as compared with anti-aminoacyl-tRNA synthetase antibodies (21). These results suggest that anti-SRP may be a marker for a specific clinical subset of patients who have particularly refractory inflammatory muscle disease.…”
Section: Discussionsupporting
confidence: 92%
“…Currently, the detection of anti-SRP autoantibodies is based on an indirect immunofluorescence test on HEp-2 cells, which typically shows a cytoplasmic pattern (1). Since this profile is not specific, the diagnosis has to be confirmed by an immunodot assay or by protein immunoprecipitation.…”
mentioning
confidence: 99%
“…16 Thus, the determination of clinical and laboratory signs for association with malignancy are of great importance for the disease prognosis. In some studies, relatively high proportions of anti-155/140 antibodies were detected in cancer-associated DM patients, and these have an excellent positive predictive value 12,13,17 Therefore, introduction of a commercial kit for this antibody to be applied in clinical screening may be beneficial. It was also shown that anti-Jo-1 antibody and cancer-associated DM, or interstitial lung disease and cancerassociated DM appear mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that anti-Jo-1 antibody and cancer-associated DM, or interstitial lung disease and cancerassociated DM appear mutually exclusive. AntiJo-1 antibody and interstitial lung disease are both associated with a specific human leukocyte antigen class II haplotype, and anti-155/140 antibody is associated with human leukocyte antigen-DQA1*0301, 17 suggesting that cancer risk in DM may be genetically determined. Thus DM patients may suffer multiple tumors due to genetic susceptibility.…”
Section: Discussionmentioning
confidence: 99%